ENKRIPSI CITRA DIGITAL BERBASIS KOMBINASI ARNOLD CAT MAP TERMODIFIKASI DAN DNA ENCODING - Yusri, Thesa Adi Saputra; Rudhistiar, Deddy (Jurnal Mnemonic, 2022)
This research was developed with the aim of improving the digital image encryption method based on the modified Arnold Cat Map with DNA encoding diffusion. The focus of this research is to analyze the performance of image randomization using a modified Arnold Cat Map that is diffused by DNA encoding. The encryption results were tested with 4 numerical parameters, namely entropy, Mean-squared error (MSE), peak signal-tonoise ratio (PSNR) and correlation coefficient. The test image is devoted to square images with size variations from 128 x 128 to 512 x 512. The results show the significance of changes in the encryption results when viewed from the histogram conditions that are evenly distributed. The average correlation value is 0.017, the average entropy is 7.9964 and the PSNR is 5.487 dB.